The subtle art of folding space - Chu, John (Writer of science fiction) (Tor Publishing Group, 2026)
"The Subtle Art of Folding Space, is the exhilarating debut science fiction novel from Nebula and Hugo Award-winning author John Chu channels unhinged physics, generational trauma, and the comfort of really good dim sum. This isn't your usual jaunt through quantum physics. Ellie's universe, and this one, is falling apart. Her ailing mother is in a coma; her sister, Chris, accuses her of being insufficiently Chinese between assassination attempts; and a shadowy cabal of engineers is trying to hijack the skunkworks, the machinery that keeps the physics of each universe working the way it's supposed to. Daniel, Ellie's cousin, has found an illicit device in the skunkworks-one that keeps Ellie's comatose mother alive while also creating destabilizing bugs in the physics of this universe. It's not a good day. If she can confront her mother's legacy and overcome her family's generational trauma, she just might find a way to preserve the skunkworks and reconcile with her sister...but digging into her family's past is thornier than it seems, and the secrets she uncovers will force Ellie to choose between her family and the universe itself"-- Provided by publisher.